PERAN TEKNOLOGI INFORMASI DALAM PERKEMBANGAN DAKWAH MAHASISWA - Yedi Purwanto; Muhamad Taufik; Asep Wawan Jatnika (Fakultas Seni Rupa dan Desain ITB, 2017)
Higher education like ITB, is expected as a pioneer in the use of application in the era of information technology nowadays, including in the Islamic Religious Education program. Information technology can be applied in the teaching and learning instruction of Islamic Religious program, as it can be used by the lecturers to deliver Islamic moral values to ITB students. In the context of Islamic preaching in higher education, ICT can be used as a medium to convey Islamic Religious materials, and it practically contributes to the development of Islamic proselytization for ITB students. As the Islamic youths, university students can take apart as the agents of change in the development of human resources to face the challenge of globalization era including the fast growth of information technology and the opened-accessibility of ASEAN Economic Community (EAC). In this context, the role of technology is crucial in overcoming these rapid changes. This paper is particularly aimed at mapping the Islamic preaching for ITB students. From this notion, it can be noted that online-social media is effective for persuading Islamic values to students. By only one posted-article, it can reach and inspire thousands readers. Besides, it is considered more effective, because the use of social media is not restricted by the specific time and place.